Gene identification using rice genome sequences - Lee, Joohyun; Koh, Hee-Jong (Genes & genomics, 2013)
Identifying useful gene(s) is one of the most important objectives of plant geneticists. Various strategies can be used, which are based on the characteristics of plant reproduction and available technology. Rice is the first model crop whose whole genome sequence has been reported. In addition, information on the whole genome sequences of two important rice subspecies (japonica and indica rice) is also available. Rice is a self-pollinating crop and methods of artificial crossing are relatively easy to perform; such methods enable the production of numerous seeds for genetic analyses. Based on these features, a map-based cloning (i.e., positional cloning) strategy has been successfully applied over the last decade to identify rice genes. Recently, advanced next-generation sequencing (NGS) technology was used to ascertain the genome sequences of individual plants, opening up a new strategy for gene identification. This strategy has been used successfully to identify the genes responsible for certain qualitative traits in rice. However, to identify the gene(s) involved in a quantitative trait, a map-based cloning strategy is still required after quantitative trait loci analysis using NGS technology. In this review, we discuss both map-based cloning (which is still the primary strategy used to identify rice genes) and NGS-based strategies.